Hand-held computers can help to distract children undergoing painful venipuncture procedures. - Crevatin, Franca; Cozzi, Giorgio; Braido, Elena; Bertossa, Gabriella; Rizzitelli, Patrizia; Lionetti, Daniela; Matassi, Daniela; Calusa, Dorotea; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2016)
AIM: Needle-related procedures can be painful for children, and distraction provides ideal pain relief in blood-drawing centres. This study assessed the effectiveness of playing a computer game during venipuncture, compared with low-tech distraction by a nurse. METHODS: We conducted this prospective, randomised controlled trial at the blood-drawing centre of a tertiary-level children's hospital in Italy. Half of the 200 children played Angry Birds on a hand-held computer while the other half were distracted by a second, specifically trained nurse who sang to them, read a book, blew bubbles or played with puppets. Pain was measured using a faces pain scale for children aged 4-7 years and a numeric scale for children aged 8-13 years. RESULTS: The 200 children had a median age of eight years. Children reported significant pain in 16 cases (16%) in the hand-held computer distraction group and in 15 cases (15%) in the nurse-led low-tech distraction group (p = 0.85). The procedural success rate at the first attempt was not different in the two groups. CONCLUSION: Playing a game on a hand-held computer meant that only one in six children reported pain during venipuncture, but it was not superior to being distracted by nurses.